Case Report: Characterizing the Role of the STXBP2-R190C Monoallelic Mutation Found in a Patient With Hemophagocytic Syndrome and Langerhans Cell Histiocytosis - Viñas-Giménez, Laura; Rincón, Rafael; Colobran, Roger; de la Cruz, Xavier; Celis, Verónica Paola; Dapena, José Luis; Alsina, Laia; Sayós, Joan; Martínez-Gallo, Mónica (Frontiers in Immunology, 2021)
Background and aims Severe forms of HLH appear early in life and are life-threatening. However, milder clinical presentations with mutations in HLH-related genes frame it as a threshold disease depending on the trigger and residual cytotoxicity of the patient's NK cells. Methods A 9-month-old child diagnosed at 2-months of age with cutaneous Langerhans cell histiocytosis. After successful treatment (Ara-C/cladribine) the patient developed a HLH episode controlled after HLH-2004 protocol. At 16-months of age the patient went through a HSCT. PCR for adenovirus was positive. NK cytotoxicity and degranulation were impaired. Genetic study revealed a monoallelic mutation in STXBP2 gene (c.568C>T/pArg190Cys). We performed COS7 transfection experiments to analyze STXBP2 expression and test the interaction with Syntaxin-11. We stablished stable RBL-2H3 cell lines expressing STXBP2wt-EGFP or STXBP2R190C-EGFP constructs to conduct the degranulation test with β-hexosaminidase. Results Mutation STXBP2R190C did not affect protein expression nor interaction with syntaxin-11. However, STXBP2R190C decreases significantly degranulation in RBL-2H3 cell line compared with STXBP2wt or non-transfected. Conclusions These results suggest that the STXBP2R190C mutation acts decreasing the ability to degranulate. Since patient showed normal degranulation between HLH episodes, it is tempting to speculate that STXBP2R190C allows sufficient residual NK degranulation to maintain balance under homeostatic conditions. However, in the context of a viral infection this residual activity would not be able to deal with it, leading to HLH. Functional testing of new mutations is essential to validate their role in genetic susceptibility to HLH and better management for these patients.